Modeling and Simulation of a Rotary Quadruple Pendulum System Using Scientific Python Stacks and Modelica Language - Adriyan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
This paper presented the modeling and simulation of a rotary quadruple pendulum (RQP) system using two open source software, i.e: scientific python stacks (SciPy stacks) and Modelica language via Anaconda python distribution and OpenModelica, respectively. The modeling stage using SymPy (a package of SciPy stacks) was conducted to obtain the governing equation in full symbolic form by applying Lagrange’s method. The listing code is also provided to test by the user later on. Meanwhile, both modeling and simulation were performed in Modelica language by addressing several conditions concerning the initial conditions of the system, i.e: examining up-up-up-up, up-up-down-down, and up-down-up-down conditions. Simulation required the numerical values of the RQP system be supplied before running the simulation. In conclusion, the derivation of the governing equation using SymPy can be done in a matter of minutes without having a mistake when doing the algebraic manipulation. Simulation using OpenModelica was present the response of the RQP system in three conditions that considered initial conditions imposed to the system. The model obtained through this research can be used a baseline for developing a control scheme for the RQP system in its inverted position.